Anaesthetic care of patients undergoing primary hip and knee arthroplasty: consensus recommendations from the International Consensus on Anaesthesia-Related Outcomes after Surgery group (ICAROS) based on a systematic review and meta-analysis. (September 2019) - Memtsoudis, Stavros G.; Cozowicz, Crispiana; Bekeris, Janis; Bekere, Dace; Liu, Jiabin; Soffin, Ellen M.; Mariano, Edward R.; Johnson, Rebecca L.; Hargett, Mary J.; Lee, Bradley H.; Wendel, Pamela; Brouillette, Mark; et al.
Abstract: Background: Evidence-based international expert consensus regarding anaesthetic practice in hip/knee arthroplasty surgery is needed for improved healthcare outcomes. Methods: The International Consensus on Anaesthesia-Related Outcomes after Surgery group (ICAROS) systematic review, including randomised controlled and observational studies comparing neuraxial to general anaesthesia regarding major complications, including mortality, cardiac, pulmonary, gastrointestinal, renal, genitourinary, thromboembolic, neurological, infectious, and bleeding complications. Medline, PubMed, Embase, and Cochrane Library including Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, NHS Economic Evaluation Database, from 1946 to May 17, 2018 were queried. Meta-analysis and Grading of Recommendations Assessment, Development and Evaluation approach was utilised to assess evidence quality and to develop recommendations. Results: The analysis of 94 studies revealed that neuraxial anaesthesia was associated with lower odds or no difference in virtually all reported complications, except for urinary retention. Excerpt of complications for neuraxial vs general anaesthesia in hip/knee arthroplasty, respectively: mortality odds ratio (OR): 0.67, 95% confidence interval (CI): 0.57–0.80/OR: 0.83, 95% CI: 0.60–1.15; pulmonary OR: 0.65, 95% CI: 0.52–0.80/OR: 0.69, 95% CI: 0.58–0.81; acute renal failure OR: 0.69, 95% CI: 0.59–0.81/OR: 0.73, 95% CI: 0.65–0.82; deep venous thrombosis OR: 0.52, 95% CI: 0.42–0.65/OR: 0.77, 95% CI: 0.64–0.93; infections OR: 0.73, 95% CI: 0.67–0.79/OR: 0.80, 95% CI: 0.76–0.85; and blood transfusion OR: 0.85, 95% CI: 0.82–0.89/OR: 0.84, 95% CI: 0.82–0.87. Conclusions: Recommendation: primary neuraxial anaesthesia is preferred for knee arthroplasty, given several positive postoperative outcome benefits; evidence level: low, weak recommendation. Recommendation: neuraxial anaesthesia is recommended for hip arthroplasty given associated outcome benefits; evidence level: moderate-low, strong recommendation. Based on current evidence, the consensus group recommends neuraxial over general anaesthesia for hip/knee arthroplasty. Trial registry number: PROSPERO CRD42018099935.